MICROBIAL AND CHEMICAL ANALYSIS OF POTABLE WATER IN PUBLIC – WATER SUPPLY WITHIN LAGOS UNIVERSITY, OJO - Ojo, O. A.; Bakare, S. B.; Babatunde, A. O. (African Journal of Infectious Diseases (AJID), 2007)
Water samples were collected especially into sterile containers (4 – litres) at four designated pints (Faculty of Science, Faculty of Arts and Social Sciences; Amala Joint and Staff School) within the Lagos State University, Ojo Campus. The water samples were immediately subjected to both chemical and microbiological analysis in order to evaluate the quality status of potable water in circulation within the university and identify its sources of contamination. Levels of iron, calcium and magnesium detectable in the circulating drinking water were far below the WHO recommended limits. However, more potentially dangerous discovery was the level of Coliform contamination which far exceeds the WHO standards. This explains the high incidence of water-borne diseases such as Dysentry, Diarrhea and Typhoid fever within the university population. Meanwhile, other micro-organisms detected were E. coli, Pseudomonas aeruginosa, Staphylococcus aureus, yeasts and moulds. The pH of potable water in circulation falls within recommended limits (6.0-8.0) but fro faculty of arts and social sciences that had pH of 5.5 which suggested a high degree of public health concern. There is the need for adequate changes to be made at points where water distribution systems integrity appeared compromised. The university community is advised to boil water before drinking in order to avoid consumption of unwholesome biological agents in the water distribution networks.